Morphological change in nucleus accumbens neurons as a basis for the development of haloperidol-induced movement disorders - De Souza, Ian Ernesto Joao (Trinity College (Dublin, Ireland). Department of Zoology, 2000)
A syndrome of involuntary, hyperkinetic abnormal movements called tardive dyskinesia (TD) develop in predisposed individuals following treatment and withdrawal from neuroleptic drugs. These movements are primarily orofacial in nature, take several weeks to develop and persist even after drug withdrawal. Rats treated chronically with classical neuroleptic drugs such as haloperidol may develop a syndrome of vacuous chewing movements (VCMs) and these have been shown to be an animal model for TD . The neural basis for the development of TD or its rat equivalent remains elusive. How ever, it is known that chronic haloperidol treatment leads to slowly developing morphological changes in neurons.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin